View of the Wachovia Bank Building under construction, 1965. - (:unkn) unknown (Forsyth County Public Library, 2008)
WSJ 2-19-65 p.1.
View of the Wachovia Bank Building under construction in the distance, 1965. The street shown at left is Second Street at the Trade Street intersection.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth